2008
DOI: 10.1093/humrep/dem382
|View full text |Cite
|
Sign up to set email alerts
|

The role of sex hormone-binding globulin and androgen receptor gene variants in the development of polycystic ovary syndrome

Abstract: The presence of long SHBG(TAAAA)n alleles is associated with increased risk for PCOS and in combination with short AR(CAG)n alleles may influence the hyperandrogenic phenotype of PCOS. This combined genotype may contribute to 'fetal programming' of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 21 publications
4
38
1
7
Order By: Relevance
“…PCOS comprises almost 90% cases of all ovulatory disorders. [5][6] Ovulation disorders often respond to simple treatments that can be safely initiated in primary care. 4 In our study, we evaluated efficacy and safety of clomiphene citrate and its combination with metformin on ovulation induction and pregnancy outcome in the treatment of anovulatory infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCOS comprises almost 90% cases of all ovulatory disorders. [5][6] Ovulation disorders often respond to simple treatments that can be safely initiated in primary care. 4 In our study, we evaluated efficacy and safety of clomiphene citrate and its combination with metformin on ovulation induction and pregnancy outcome in the treatment of anovulatory infertility.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS affects approximately 5-10% of the female population in developed countries. 5,6 Women with this syndrome have hyperandrogenism, morphologic changes in the ovary (polycystic), inappropriate gonadotropin secretion (elevated levels of circulating luteinizing hormone), and insulin resistance with accompanying compensatory hyperinsulinemia.…”
Section: Introductionmentioning
confidence: 99%
“…The most striking evidence demonstrating AR (CAG) n as a leading causal factor of ovarian hyperandrogenism was demonstrated in a follow-up study on Spanish girls. Ibanez et al found that girls with premature pubarche and subsequent ovarian hyperandrogenism exhibited a shorter AR (CAG) n repeat length compared with healthy controls (12), while another investigator insisted that shorter CAG repeats heighten androgen levels only when combined with longer alleles of SHBG (TAAAA) n pentanucleotide polymorphism (24).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, genetically determined low SHBG levels may provide the genetic link for the developmental origin hypothesis of PCOS ( Abbott et al, 2002, Xita andTsatsoulis 2006). Further studies in the same cohort of women with PCOS, revealed that the combination of long SHBG(TAAAA)n repeat alleles with either a short microsatellite (TTTA)n repeat allele of aromatase gene or a short (CAG)n repeat allele of the androgen receptor gene has a synergistic effect on the hyperandrogenic phenotype of PCOS (Xita et al, 2008a;Xita et al, 2008b).…”
Section: The (Taaaa)n Repeat Polymorphism In Shbg Promotermentioning
confidence: 99%